Uncovering the genetic basis of natural variation of leaf form in Cardamine hirsuta - Lamb, J (2015)
A major goal in biology is to understand the genetic basis of morphological variation at different evolutionary scales, for example between and within species. Here I investigate this issue by using plant leaves as an example. Previously comparative studies between the simple leaf model plant Arabidopsis thaliana and its dissected leaf relative Cardamine hirsuta have shown that inter-specific differences in leaf shape mostly result from variation in local tissue growth and patterning (Vlad et al., 2014; Hay et al., 2006; Barkoulas et al., 2008). Here, I aim to elucidate the genetic basis of natural variation in leaf form within species, by using divergent strains of C. hirsuta. I present evidence that variation in six strains collected from geographically diverse locations results from different rates of progression of an age-dependent leaf development programme in a phenomenon known as heteroblasty. By using Quantitative trait loci (QTL) mapping with a recombinant inbred line (RIL) population derived from a cross between the Oxford and Azores strains, I detected six QTL that influence leaflet production on multiple leaves. A QTL located on the 4th linkage group was validated and selected for further analysis. Characterisation of QTL effect indicated that the QTL influences leaf form by altering the rate of heteroblastic development. Subsequently I fine mapped this QTL to a DNA segment of 48 kb containing the gene SQUAMOSA PROMOTER PROTEIN BINDING LIKE 9 (ChSPL9), a previously characterised regulator of age dependent development. The parental alleles of ChSPL9 show variation in their sequence and were transformed into A. thaliana to evaluate whether they contribute to the QTL effect. Resultant phenotypes mirrored the QTL effect suggesting that ChSPL9 does indeed contribute to this QTL effect. These results indicate that age-dependent leaf shape progression underlies variation in leaflet number within species and more broadly suggest that in the case of plant leaves different processes might underlie morphological variation between and within species.